Soil Phosphorus Fractionation as Affected by Paper Mill Biosolids Applied to Soils of Contrasting Properties - Zhang, Xiangru; Gagnon, Bernard; Ziadi, Noura; Cambouris, Athyna N.; Alotaibi, Khaled D.; Hu, Zhengyi (Frontiers in Environmental Science, 2020)
Industrial by-products like paper mill biosolids (PB) have been used as fertilizers and amendments in agriculture for many decades. However, their content of plant essential nutrients including phosphorus (P) varies largely with sources and availability of these nutrients once applied to soil still remains unknown. Five PB differing in their C/N ratio were used in an incubation study to assess the P forms and availability from both PB and PB-amended soils. Biosolids were added to three contrasting soils in 500-mL jars at the rate of 50 Mg wet ha-1, supplying between 36 and 113 kg total P ha-1. An unfertilized control was also included. Biosolids and soil P fractions were determined by a modified Hedley fractionation method following two and 16 weeks of incubation. Phosphorus forms in PBs varied with type of materials with labile P ranging from 20 to 72% and organic P (Po) ranging from 28 to 66% of total P. Soil incubated with PB showed changes in all P fractions due to amendment, soil types and duration of incubation. Resin-P and labile P, the most available forms, were significantly higher with addition of high PB-P content. Soil labile P represented up to 50% of total P added by PB. Overall, most inorganic P (Pi) fractions and labile P further increased with incubation duration. Close relationships were established between resin-P and labile P content in PB and the increases of those fractions in incubated soils, notably after two weeks. We concluded that some PB could be used as efficient sources of P for fertilizing crops.